A critical analysis of walking policy in Ireland and its contribution to both national and international development goals - Dylan Power; Dylan Power; Barry Lambe; Niamh Murphy (Frontiers in Sports and Active Living, 2023)
IntroductionIncreasing population levels of walking holds benefits for public and planetary health. While individual level interventions to promote walking have been shown to be efficacious, upstream interventions such as policies harness the greatest potential for impact at the population level. However, little is known about the nature and presence of walking policy in Ireland and the extent to which it aligns to national and global goals. This paper aims to provide an overview of local and national walking policy in Ireland and to understand the potential of Irish walking policy to contribute to national and global targets.MethodsThis study used multiple methods to provide a critical overview of walking policy. Firstly, a six-phase process was employed to conduct a content analysis of local and national walking policy in Ireland. Secondly, conceptual linkage exercises were conducted to assess the contribution of walking, and national walking policy in Ireland, to Ireland's National Strategic Outcomes and the United Nations Sustainable Development Goals.ResultsOverall, half (n = 13) of the counties in the Republic of Ireland were found to have no local level walking policies. Results from the content analysis suggest that counties which had walking specific local level policies (n = 2) were outdated by almost two decades. Walking was identified to hold the potential to contribute to over half (n = 6) of Ireland's National Strategic Outcomes, and over half (n = 7) of the United Nations Sustainable Development Goals. Ireland's only national level walking specific policy, the Get Ireland Walking Strategy and Action Plan 2017–2020, was identified to potentially contribute to four of Ireland's National Strategic Outcomes and three United Nations Sustainable Development Goals.DiscussionMultidisciplinary action is required to update walking-related policy with embedded evaluation and governance mechanisms in all local walking systems. Furthermore, given sufficient collaboration across sectors, walking policy in Ireland has the potential to contribute to a wider breadth of national and global targets beyond the health, sport, tourism, and transport sectors.